Impact of a colorectal enhanced recovery program implementation on clinical outcomes and institutional costs: A prospective cohort study with retrospective control. (May 2018) - Portinari, Mattia; Ascanelli, Simona; Targa, Simone; Dos Santos Valgode, Elisabete Maria; Bonvento, Barbara; Vagnoni, Emidia; Camerani, Stefano; Verri, Marco; Volta, Carlo Alberto; Feo, Carlo V.
Abstract: Background: The enhanced recovery program for perioperative care of the surgical patient reduces postoperative metabolic response and organ dysfunction, accelerating functional recovery. The aim of this study was to determine the impact on postoperative recovery and cost-effectiveness of implementing a colorectal enhanced recovery program in an Italian academic centre. Materials and methods: A prospective series of consecutive patients (N = 100) undergoing elective colorectal resection completing a standardized enhanced recovery program in 2013–2015 (ERP group) was compared to patients (N = 100) operated at the same institution in 2010–2011 (Pre-ERP group) before introducing the program. The exclusion criteria were: >80 years old, ASA score of IV, a stage IV TNM, and diagnosis of inflammatory bowel disease. The primary outcome was hospital length of stay which was used as a proxy of functional recovery. Secondary outcomes included: postoperative complications, 30-day readmission and mortality, protocol adherence, nursing workload, cost-effectiveness, and factors predicting prolonged hospital stay. The ERP group patient satisfaction was also evaluated. Results: Hospital stay was significantly reduced in the ERP versus the Pre-ERP group (4 versus 8 days) as well as nursing workload, with no increase in postoperative complications, 30-day readmission or mortality. ERP group protocol adherence (81%) and patient satisfaction were high. Conventional perioperative protocol was the only independent predictor of prolonged hospital stay. Total mean direct costs per patient were significantly higher in the Pre-ERP versus the ERP group (6796.76 versus 5339.05 euros). Conclusions: Implementing a colorectal enhanced recovery program is feasible, efficient for functional recovery and hospital stay reduction, safe, and cost-effective. High patient satisfaction and nursing workload reduction may also be expected, but high protocol adherence is necessary. Highlights: Implementing an ERP in elective colorectal surgery: Significantly reduced time to functional recovery and postoperative hospital LOS with high patient satisfaction. Did not increase morbidity, mortality, and 30-day readmission rates. Significantly decreased both institutional costs and nursing workload.